Psychiatric Approach Management of Ambiguous Genitalia in Children and Teenagers - Popy Arizona; Nining Febriyana; Budi Kristianto (Faculty of Medicine, Universitas Airlangga, 2023)
AbstractIntroductions: Ambiguous genitalia is a congenital disorder defined by atypical development at the chromosomal, gonadal, or anatomical levels of the sex organ. The incidence of ambiguous genitalia is estimated to be 1 in 4500-5500 births. The management of ambiguous genitalia takes an extended time. This can lead to psychiatric manifestations such as depression, anxiety, suicidal ideation, and substances. Objectives: The study aimed to describe the management of ambiguous genitalia in the scope of psychiatry to optimize the comprehensive treatment of the disorder and achieve a good quality of life for a person with ambiguous genitalia in Indonesia. Methods: This study is a literature review that collects from various sources of scientific journals related to the psychiatric management of the disorder. Results: Ambiguous genitalia should be treated by a multidisciplinary approach, with a mental health professional and other essential expertise of the team. Improper application of parenting in childhood can create a problem in adolescence and adulthood. Certain aspects of the management need a psychiatrist’s assistance. Psychological management should focus on giving reliable information that is not confusing and preparing children and adolescents to encounter general and sexual life problems. The family and the child should always be involved during the process. Conclusions: The purpose of the entire ambiguous genitalia treatment is to strengthen the patient and family’s adaptive coping to the stressors correlated with ambiguous genitalia and the management to promote good quality of life for children and adolescents.